"Lest on too close sight I miss the darling illusion": The Politics of the Centre in "Reading Maritime" - Tremblay, Tony (Studies in Canadian Literature, 2008)
Postcolonial theories of centre-margin dynamics, such as those expressed by Chinua Achebe and Slavoj Zizek, suggest the need to read Canadian regionalism "backward" – "as a construction of the centre rather than the margins" and as linked to constraining demands for authorial intelligibility. An examination of central Canada's critical reception of writers such as Alistair MacLeod and David Adams Richards reveals how the phenomenon of "writing region" has worked to create a theoretical model of "Maritimeness" that outside readers desire.